2022
DOI: 10.1007/s00484-022-02332-z
|View full text |Cite
|
Sign up to set email alerts
|

Visits to the accident and emergency department in hot season of a city with subtropical climate: association with heat stress and related meteorological variables

Abstract: Background Literature reporting the association between heat stress defined by universal thermal climate index (UTCI) and emergency department visits is mainly conducted in Europe. This study aimed to investigate the association between heat stress, as defined by the UTCI, and visits to the accident and emergency department (AED) in Hong Kong, which represents a subtropical climate region. Methods A retrospective study involving 13,438,846 AED visits in the public secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Females are a population at risk for asthma ED visits. A previous study showed that extreme weather events increased the risk of asthma ED visits by females by 4.10-fold (95% CI 2.60‒5.60; p<0.05) [ 71 ]. Stress and anxiety have been linked to asthma ED visits and females may be more likely to experience these during extreme weather events [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Females are a population at risk for asthma ED visits. A previous study showed that extreme weather events increased the risk of asthma ED visits by females by 4.10-fold (95% CI 2.60‒5.60; p<0.05) [ 71 ]. Stress and anxiety have been linked to asthma ED visits and females may be more likely to experience these during extreme weather events [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extreme hot weather brings negative impacts on people's health and wellbeing ( 6 , 7 ). In Hong Kong, it has been reported that extreme hot weather events are related to higher risk of adverse health outcomes such as mortality ( 8 , 9 ), asthma hospitalization ( 10 ) acute myocardial infarction among patients with diabetes mellitus ( 11 ), all-cause accident and emergency department visits ( 12 ) and suicide deaths ( 13 ). Moreover, the impact of extreme hot temperature could be more serious for the vulnerable groups in the population.…”
Section: Introductionmentioning
confidence: 99%